2021
DOI: 10.1111/cns.13611
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in ischemic stroke

Abstract: The pathophysiological mechanisms of neuroinflammation, angiogenesis, and neuroplasticity are currently the hotspots of researches in ischemic stroke. Regulatory T cells (Tregs), a subset of T cells that control inflammatory and immune responses in the body, are closely related to the pathogenesis of ischemic stroke. They participate in the inflammatory response and neuroplasticity process of ischemic stroke by various mechanisms, such as secretion of anti‐inflammatory factors, inhibition of pro‐inflammatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 98 publications
(246 reference statements)
2
36
0
Order By: Relevance
“…Lymphocytes have less important contributions in cerebral ischemic injury; the mechanisms are mainly related to the innate T cell functions [ 103 ]. IL-17 secreting γδT cells, CD4 + T cells, and CD8 + T cells may infiltrate the parenchyma within hours after stroke onset, peak by day 3, and aggravate ischemic injury [ 68 , 103 , 104 ], as do natural killer T cells [ 105 ], while regulatory lymphocytes (Tregs) expressing the forkhead box P3 (Foxp3) transcription factor [ 106 , 107 ] have traditionally been regarded as exhibiting neuroprotective activity [ 108 , 109 ]. The choroid plexuses appear to be the preferential route for infiltration by lymphocytes since in an experimental setting, infarction of the choroid plexus resulted in diminished lymphocyte infiltration [ 110 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…Lymphocytes have less important contributions in cerebral ischemic injury; the mechanisms are mainly related to the innate T cell functions [ 103 ]. IL-17 secreting γδT cells, CD4 + T cells, and CD8 + T cells may infiltrate the parenchyma within hours after stroke onset, peak by day 3, and aggravate ischemic injury [ 68 , 103 , 104 ], as do natural killer T cells [ 105 ], while regulatory lymphocytes (Tregs) expressing the forkhead box P3 (Foxp3) transcription factor [ 106 , 107 ] have traditionally been regarded as exhibiting neuroprotective activity [ 108 , 109 ]. The choroid plexuses appear to be the preferential route for infiltration by lymphocytes since in an experimental setting, infarction of the choroid plexus resulted in diminished lymphocyte infiltration [ 110 ].…”
Section: Inflammation In Ischemia/reperfusion Injuriesmentioning
confidence: 99%
“…Contrary, Kleinschnitz et al ( 2013 ) found a marked increase of Foxp3 + Tregs in the brain within 24 h after tMCAO, but predominantly in the cerebral vasculature. Tregs play a double-edged role in IS, but primarily with a neuroprotective effect (Wang H. et al, 2021 ). Brain Tregs can modulate the microglia/macrophages polarization toward M2-type in cerebral ischemia by secreting IL-10 and TGF-β, therefore protecting against secondary brain damage (Liesz et al, 2009 ; Liu et al, 2011 ).…”
Section: The Communication Between Microglia and Cns-infiltrating Cellsmentioning
confidence: 99%
“…Studies conducted on cardiovascular diseases, e.g., atherosclerosis, hypertension, acute coronary syndrome, and stroke, have indicated that immunosuppressive cells were involved in the pathology of CVD [ 116 119 ]. For instance, the occurrence of a stroke increased the level of Tregs which attenuated inflammatory responses and enhanced the appearance of post-stroke regeneration [ 119 , 120 ]. Accordingly, stroke increased the level of circulating M-MDSCs in human stroke patients [ 121 ].…”
Section: Clinical Interactions Between Aging and Chronic Inflammatory...mentioning
confidence: 99%